Aktivasi Invasi dan Metastasis: Tinjauan Artikel - Muhammad Dodik Prastiyo (Kelompok Ilmiah Hippocrates Fakultas Kedokteran Universitas Udayana, 2024)
Cancer is a global problem worldwide with high mortality rates. The process of cancer is studied more specifically in Hallmark of cancer. Hallmarks of cancer explains that there is one trait of cancer, namely tissue invasion and metastasis. The hallmarks of cancer tissue invasion and metastasis is responsible for >90% of cancer deaths, so this article examines how the process of invasion and metastasis in cancer development.